Ecological Distribution and Diversity of Key Functional Genes for Denitrification in Surface Sediments of the Northern South China Sea: Implications for Potential N2O Emissions - Xiang, Hua; Hong, Yiguo; Wu, Jiapeng; Long, Aimin (Frontiers in Marine Science, 2022)
Denitrification is an important pathway for nitrogen sink and N2O emissions, but little is known about the ecological distribution of key functional genes of denitrification and their potential N2O emissions in marine sediments. In this study, we analyzed the abundance, ecological distribution, and diversity of key functional genes (nir and nosZ) for denitrification in the northern South China Sea (SCS) surface sediments. Our results showed that the gene abundances varied from 105 to 108 and from 106 to 107 copies·g-1 for the nirS and nirK, respectively. The nosZ II/nosZ I gene abundance ratios were 1.28–9.88 in shallow-sea and deep-sea sediments, suggesting that the nosZ II gene should play a dominant role in N2O reduction in the northern SCS sediments. Moreover, the significantly higher abundance ratios of nir/nosZ in deep-sea surface sediments implied that there might be stronger N2O emissions potential in deep-sea sediments than in shallow-sea sediments. The ecological distribution profiles of the nirS, nosZ I, and nosZ II gene communities varied with water depth, and denitrification genes in shallow-sea and deep-sea sediments differed in their sensitivity to environmental factors. Water temperature was the major factor affecting both the abundance and the community distribution of the nirS gene in deep-sea sediments. Nitrate was the major factor shaping the community of nosZ I and nosZ II genes in shallow-sea sediments. Our study provides a pattern of ecological distribution and diversity for the nir and nosZ genes and emphasizes the role of these key functional genes in potential N2O emissions of the northern SCS surface sediments.